2018
DOI: 10.1371/journal.pone.0208853
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the pks3 gene of Aurantiochytrium limacinum and functional study of the 3-ketoacyl-ACP reductase and dehydratase enzyme domains

Abstract: Aurantiochytrium limacinum has received attention because of its abundance of polyunsaturated fatty acids (PUFAs), particularly docosahexaenoic acid (DHA). DHA is synthesized through the polyketide synthase (PKS) pathway in A. limacinum. The related enzymes of the PKS pathway are mainly expressed by three gene clusters, called pks1, pks2 and pks3. In this study, the full-length pks3 gene was obtained by polymerase chain reaction amplification and Genome Walking technology. Based on a domain analysis of the ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The transferred genetic material can be either a circular [125] or a linearized plasmid [126], or just the amplified cassette with the flanking regions for the homologous recombination [127]. With these methods, overexpressing [128], knocked-in [129], and disrupted [104] mutants have been obtained. To improve the efficiency of transformation, the cell wall can be weakened by DTT treatments [130], by vortexing cells with zircon beads before resuspension with the amplified DNA construct [127], or by incubation for few hours with a cocktail of various cell-wall degrading enzymes [126].…”
Section: Engineering the Metabolism Of Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transferred genetic material can be either a circular [125] or a linearized plasmid [126], or just the amplified cassette with the flanking regions for the homologous recombination [127]. With these methods, overexpressing [128], knocked-in [129], and disrupted [104] mutants have been obtained. To improve the efficiency of transformation, the cell wall can be weakened by DTT treatments [130], by vortexing cells with zircon beads before resuspension with the amplified DNA construct [127], or by incubation for few hours with a cocktail of various cell-wall degrading enzymes [126].…”
Section: Engineering the Metabolism Of Lipidsmentioning
confidence: 99%
“…In an attempt to modify the PUFA synthase activity in Aurantiochytrium limacinum, the KR and DH domains of the subunit A (Fig. 7) were separately overexpressed by knock-in strategies [129]. In these mutants, the total content of PUFAs is only marginally increased, but the amount of 20:4 (ARA), a minor FA in A. limacinum, is nearly doubled.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…1 , the putative domains and active sites of the PKS gene cluster were identified by several online bioinformatic analysis tools, including BLAST (NCBI), SMART [ 8 ] and PKS/NRPS analysis [ 9 ]. Recently, research on the synthetic ability of PKS gene cluster to improve microbial strains and characterize their synthetic pathways has become a research hotspot [ 10 – 12 ]. Hayashi et al investigated the function of ACPs and found that the number of activated ACPs increased the productivity of PUFA [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These were different for each gene on the cassette, potentially intended to avoid intramolecular HR that can truncate the plasmids [ 119 ]. One exception is that two copies of the same phosphoglycerate kinase (PGK) promoter were used on the same cassette without negative consequences mentioned in A. limacinum OUC168 [ 29 ].…”
Section: The Properties Of the Dna Related To Gene Expression In Thraustochytridsmentioning
confidence: 99%
“… ( a ) The number of successfully engineered thraustochytrid strains by one or more methods (electroporation [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], biolistic transformation [ 5 , 27 , 53 , 54 , 55 ], and others [ 56 , 57 , 58 , 59 ]) ( Tables S1 and S2 ). The doughnut pie charts indicate the proportion of different genera.…”
Section: Figurementioning
confidence: 99%